THE STRATEGY DEVELOPMENT FOR LEADERSHIP SKILLS IN THE 21st CENTURY AT THE DEPARTMENT LEVEL UNDER THE MINISTRY OF EDUCATION AND SPORTS LAO PEOPLE’S DEMOCRATIC REPUBLIC - Phinsawat, Southanom; Thurisut, Tanakrit; Suksan, Bussagorn (Journal of Buddhist Anthropology, 2021)
The objectives of this article were to: 1) study current conditions and expectations for leadership skills development, department supervisor level, 2) formulate the strategy development for leadership skills in the 21st Century, and 3) evaluate and disseminate the strategy of 21st Century. This research was a research and development model with 3 phases: Phase 1: to study current conditions and expectations for leadership skills development, sample group are department supervisor level as representatives from department supervisor level of 290 people, using questionnaire. By statistics of percentage, average and standard deviation, Phase 2: to formulate the strategy development for leadership skills in the 21st Century, become qualified person with knowledge and ability to develop for leadership skills. Use in-depth interviews and focus group discussions for 20 people, by content analysis, and Phase 3: to evaluate and disseminate the strategy of 21st Century, become qualified person with knowledge and ability to develop leadership skills, using assessment of 30 people, from the parent contributor group with a purposive sampling, using statistics of percentage, average and standard deviation and summarizing as an overview. The research found that: 1) the current conditions for leadership skills development ( = 4.24, S.D. = 0.65), and expectations ( = 4.54, S.D.= 1.17), the overall a high level, PNI Modified 0.02 - 0.10 and the mean was the highest in decision-making and followed by Social building, 2) the formulate a leadership skills development strategy consists: vision, mission, goals and strategic issues, there are 3 issues: 2.1) self-management and development, department supervisor level, 2.2) administration and development, department supervisor level, and 2.3) management and social development in the organization, department supervisor level, and 3) the an evaluate and disseminate the strategy for leadership skills development. There are reasonable and possibility, an average of more than >3.51 or higher level, considered to pass the assessment criteria.